(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The software platform that is going to spread all over the world should be available in several languages without compromising its performance and consistency. A significant technical issue is the control over the process of static translation and dynamic user-generated content. This paper introduces a hybrid multi-lingual translation model that is a combination of the datastore based static translations and AI based dynamic translation services. The suggested system employs language preference management, caching and decision logic in order to trade off between accuracy and response time. A quantitative comparison is made between the hybrid system and a translation strategy of the system that is static only in various languages including low-resource languages. They found that performance is better in the form of increased accuracy of translation, reduced fallback rates, and increased system performance. The results indicate that the hybrid translation structures are suitable to the contemporary global software platforms.